EFEKTIVITAS IMPLEMENTASI ALOKASI DANA DESA (ADD) DALAM MENINGKATKAN PEMBANGUNAN FISIK DI DESA LINSOWU KABUPATEN BUTON UTARA - Devi, Devi; Basri, Muhammad; Muhammad Elwan, La Ode (REZ PUBLICA, 2019)
This study aims to determine the Effectiveness of the Implementation of Village Fund Allocation(ADD) in Improving Physical Development of Linsowu Village, Kulisusu District, North ButonRegency and to determine the factors that influence its implementation. The researchthe method used is a quantitative approach, with the type of data sources used in this study areobservation and in-depth interviews using the questionnaire and library guides. Based on theresults of the study, the stages of achieving the objectives of the allocation of village funds inthe village of Linsowu physical development at the integration stage is quite good, successfuland very beneficial to the community, the process of village government socialization iscarried out through meetings, at the last stage namely work adaptation, the villagethe government in Linsowu unable to adjust because of the village government human resourcesare still very low but following training, the village government starts to make improvementsperiodically. Factors that influence the implementation of village fund allocations inenhancing Physical Development in Linsowu Village in general support and contribute in thecontext of physical development.